Problems with the application of conventional financial ratios in corporate risk measurement - Fenyves , Veronika (Applied Studies in Agribusiness and Commerce, 2013)
One of the enterprises’ biggest fears is a potential bankruptcy situation. This is the reason there are a lot of people who try to anticipate it. To be aware of the actual and expected future situation of a company is in the interest of all those who are related. This topic has come to the fore after the economic and financial crisis of 2008. Companies, their creditors and internal stakeholders should be aware of the liquidity and solvency situation of a given company, because its deterioration can cause serious problems for all of them. During the financial analysis of companies, the problem of liquidity indicators showing bad signals can often be experienced, although there is no visible sign of difficulty in their operation. In other cases, the situation is just the opposite, i.e. liquidity ratios are adequate, but still, the business faces payment issues. How could it happen? The purpose of this study is to present indicators which can measure more accurately and reliably the actual liquidity position of a company.